Electrodeposition of poly (vinyl alcohol-co-ethylene) nanofiber reinforced chitosan nanocomposite film for electrochemically programmed release of protein. (10th April 2020) - Yan, Kun; Xu, Feiyang; Ni, Yongheng; Yao, Ke; Zhong, Weibing; Chen, Yuanli; Wang, Dong
Abstract: Here, we report that chitosan can mediate assembly of poly (vinyl alcohol- co -ethylene) (PVA- co -PE) nanofiber via a green and facile electrodeposition approach, and forming a nanocomposite film with enhanced mechanical property and pH-dependent permeability. Several measurements suggest the film growth (eg. thickness) is linearly correlated to the imposed charge transfer and can be well quantified by using a moving front model. Morphological observations reveal that the nanofibers are evenly distributed throughout of the films and formed with novel fiber/polymer architecture. Swelling ratio and water flux measurements indicate the film permeation property was greatly influenced by the nanofiber contents and environmental pH cues. The incorporated nanofiber leads to a higher protein loading capacity of 1.38 μg/cm 2 (eg. Insulin) and allows a sustained release from the confined internal microporous structure over 24 h. In addition, above release behaviors can be programmed according to externally imposed electrical signals. Thus, coupling chitosan-mediated assembly of nanofibers with the electrochemically controlled release system provides great possibilities for multi-functional coatings and drug elution on conductive implants. Graphical abstract: Image 1 Highlights: The PVA- co -PE/chitosan nanocomposite was successfully constructed via a green and facile electrodeposition method. The nanofiber is confirmed to influence greatly on the film structure and properties. The incorporated nanofiber network confers higher mechanical property and pH-dependent permeation performance to the film. The nanocomposite was proved to be a versatile platform for electrochemically programmed release of protein.